1997
DOI: 10.1007/s004840050058
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bright light for several hours during the daytime lowers tympanic temperature

Abstract: The present study investigates the effect on thympanic temperature of exposure to different light intensities for several hours during the daytime. Nine healthy young adult volunteers (two male, seven female) were exposed to bright light of 4000 lx or dim light of 100 lx during the daytime from 0930 to 1800 hours; the light condition was then kept at 100 lx for a further hour. Tympanic temperature was measured continuously at a neutral condition (28 degrees C, 60% relative humidity) from 1000 to 1800 hours. Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…Therefore, tympanic temperature is often used as an indicator to explain the changes of autonomic and behavioral temperature regulation (Cabanac, 1995). Thus, such different sensitivity between tympanic and rectal temperatures might be probably responsible for different core temperature during the daytime between our present experiment and the one by Aizawa and Tokura (1997). In our experiment, the level of rectal temperature during the nighttime was not different between the two light conditions.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Therefore, tympanic temperature is often used as an indicator to explain the changes of autonomic and behavioral temperature regulation (Cabanac, 1995). Thus, such different sensitivity between tympanic and rectal temperatures might be probably responsible for different core temperature during the daytime between our present experiment and the one by Aizawa and Tokura (1997). In our experiment, the level of rectal temperature during the nighttime was not different between the two light conditions.…”
Section: Discussionsupporting
confidence: 47%
“…Our results during the daytime were consistent with their findings. On the contrary, Aizawa and Tokura (1997) found that exposure to bright light during the daytime made the tympanic temperature lower significantly in a few hours after light application. These discrepancies probably seemed to reflect the different sensitivity to internal and external stimuli between rectal and tympanic temperatures (Cabanac and Caputa, 1979).…”
Section: Discussionmentioning
confidence: 73%
“…The most important finding is that tympanic temperature gradually decreases slightly, but significantly if the participants spend time under constant bright light (more than 2,000 lx) for several hours during the daytime, compared with dim light (less than 100 lx) (Aizawa and Tokura, 1997, 1998a, 1998b. Similar change may be valid for rectal temperature (Sato et al, 2003).…”
Section: Introduction-light and Core Temperature-supporting
confidence: 53%
“…Subjects practiced attaching the sensors several times before experiments. It has been reported that tympanic temperature was affected by ambient illuminance (Aizawa et al, 1997). Horizontal illuminance at the working plane in front of the subject was 909 lx from four fluorescent tubes on the ceiling, which was within the Japanese Industrial Standard (JIS) recommended illuminance range for office work.…”
Section: Measured Variablesmentioning
confidence: 95%